An analysis of the effect of board characteristics and the pandemic on sustainability performance among emerging markets - Garcia, Ma. Beatrice Emmanuelle Z. (Animo Repository, 2022)
Corporate governance, being a structure that directs and controls corporations, has been the focus of many scholars due to its broad influence on firm performance, policies, and more. This fact is globally relevant to investors and stakeholders alike as their traits and inclinations as a group are consequential to the continuous development of corporations. Likewise, it is all the more important for companies in emerging markets since it is a key initiative to encourage positive firm behavior in these companies. The main focus of this study is to determine the effect of corporate governance on sustainability performance, to be identified through 793 publicly-listed companies within emerging markets. This amounted to a total of 7,137 observations comprising twenty-four (24) countries over the period of nine (9) years, 2013 to 2021 (Pre-Covid & During Covid). Corporate governance will be proxied by board characteristics which includes board size, board gender diversity, board independence, and CEO duality. On the other hand, the sustainability performance will be measured through the use of the environmental, social, and governance (ESG) scores. This study will utilize secondary data obtained from Thomson Reuters Refinitv Eikon database. Moreover, the panel data regression model will be employed as the statistical tool to determine the effect of board characteristics on sustainability performance over time, across different emerging markets all over the world. Findings from the statistical analysis showed that all the independent variables have significant effects on sustainability performance. Specifically, board independence and gender diversity was observed to have positive effects on ESG scores as external directors and increasing female representation encourages discussions involving environmentally and socially inclined initiatives. On the other hand, board size and CEO duality was determined to have significant negative effects on ESG scores. It was observed that the larger the board and the duality of being both CEO and chairman serves as factors that hinders management progression due to the lack of coordination and a conflict of interest; that of which includes efforts on sustainability. The findings of this study addresses the gap in empirical evidence on the subject of corporate governance, specifically board characteristics, and sustainability performance within emerging markets. In addition, a global perspective was utilized which includes observations from the recent COVID-19 pandemic.